Nilai Perjuangan Dalam Film Hafalan Shalat Delisa Serta Implikasinya Terhadap Pembelajaran Drama Peserta Didik SMP Kelas VIII - Dewi Fitriah; Misnawati Misnawati; Indra Perdana; Albertus Purwaka; Syarah Veniaty (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The general research objective is to obtain an overview of the value of struggle in a film and to find out its implications for drama learning for Grade VIII students of junior high school. This study uses a qualitative descriptive analysis approach, in which the researcher records carefully and carefully the data in the form of words, sentences, pictures, and videos..Researchers found 40 values ​​of struggle in the film Memorization of Shalat Delisa and have described their implications for drama learning for class VIII students. The value of the struggle that was found the most was the value of the struggle for patience consisting of 19 data and the value of the struggle for the unyielding spirit consisting of 11 data, while the least was the value of the struggle for cooperation consisting of 5 data and the value of the struggle for mutual help consisting of 5 data. The film Memorization of the Delisa Prayer provides many descriptions of the value of struggle that can be presented as examples for students at school.